Mr 46,000 mannose 6-phosphate specific receptor: its role in targeting of lysosomal enzymes. - Stein, M (1987)
Antibodies that block the ligand binding site of the cation-dependent mannose 6-phosphate specific receptor (Mr 46,000 MPR) were used to probe the function of the receptor in transport of lysosomal enzymes. Addition of the antibodies to the medium of Morris hepatoma 7777 cells, which express only the Mr 46,000 MPR, resulted in a decreased intracellular retention and increased secretion of newly synthesized lysosomal enzymes. In fibroblasts and HepG2 cells that express the cation-independent mannose 6-phosphate specific receptor (Mr 215,000 MPR) in addition to the Mr 46,000 MPR, antibodies against the Mr 46,000 MPR inhibited the intracellular retention of newly synthesized lysosomal enzymes only when added to the medium together with antibodies against the Mr 215,000 MPR. Morris hepatoma (M.H.) 7777 did not endocytose lysosomal enzymes, while U937 monocytes, which express both types of MPR, internalized lysosomal enzymes. The uptake was inhibited by antibodies against the Mr 215,000 MPR, but not by antibodies against the Mr 46,000 MPR. These observations suggest that Mr 46,000 MPR mediates transport of endogenous but not endocytosis of exogenous lysosomal enzymes. Internalization of receptor antibodies indicated that the failure to mediate endocytosis of lysosomal enzymes is due to an inability of surface Mr 46,000 MPR to bind ligands rather than its exclusion from the plasma membrane or from internalization.